Mibanco: specialized banking products and services for micro and small scale entrepreneurs - Franco Concha, Pedro (2007)
Mibanco is a Peruvian micro finance institution with 74 offices nationwide. It was the first commercial bank in Peru, and second in Latin America, with its core business focused on providing financial services to lower income households and their micro and small enterprises. Since assuming operations in 1998, Mibanco has loaned over US$1,630 million in amounts ranging from US$100 to US$1500. Starting from a base in Lima, Mibanco spread operations nationwide, including rural areas. This case examines the challenges Mibanco experienced in offering credit to people who had never had access to the formal banking system in Peru and its innovations contributing to its success. This case also describes Mibanco’s latest adaptations in response to growing competition in the lower income market.